2020
DOI: 10.1002/marc.202000049
|View full text |Cite
|
Sign up to set email alerts
|

Adamantane‐Terminated Polypeptides: Synthesis by N‐Carboxyanhydride Polymerization and Template‐Based Self‐Assembly of Responsive Nanocontainers via Host–Guest Complexation with β‐Cyclodextrin

Abstract: The synthesis of adamantane‐terminated polypeptides by N‐carboxyanhydride (NCA) polymerization and their use in the template‐based self‐assembly of redox‐responsive nanocontainers is described. Cyclodextrin vesicles (CDV) serve as a supramolecular template to anchor adamantane terminated polypeptides on to the surface of CDV and to form polypeptide shelled vesicles (PPSVss) which are stabilized by crosslinking with cystamin. Polypeptides are characterized by nuclear magnetic resonance, matrix‐assisted laser de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…For the synthesis of Ad terminated polymer, Ad methyl amine (Ad‐NH 2 ) was chosen as the initiator. NCA polymerization of ZLL monomer by this initiator, followed by deprotection of the amines, gave Ad‐PLL as reported in our previous publication [10a] …”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…For the synthesis of Ad terminated polymer, Ad methyl amine (Ad‐NH 2 ) was chosen as the initiator. NCA polymerization of ZLL monomer by this initiator, followed by deprotection of the amines, gave Ad‐PLL as reported in our previous publication [10a] …”
Section: Resultssupporting
confidence: 69%
“…This is likely due to the higher molecular weight of Ad‐PLL 52 , which makes the CD cavities inside the NGs inaccessible. In a recent publication, we showed that Ad terminated polypeptides such as Ad‐PLL 52 are able to form host guest complex with β‐CD with a binding affinity, K≈5×10 4 M −1 [10a] . This finding implies that the presence of the polymer on Ad‐PLL 52 does not hinder the host guest interaction of Ad and CD.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, the CD has a hydrophobic cavity, providing an ideal microenvironment for the enzyme. Among the extensive range of host-guest complexes, the adamantane-β-CD inclusion complex [160] is especially useful in the design of electrochemical-based biosensors [161,162]. The CD adamantane host-guest complex serves to dock the biological recognition element of the sensor, facilitating its recognition of the target analyte.…”
Section: Cyclodextrin-based Biosensorsmentioning
confidence: 99%